Associations Between Residential Treatment Length, PTSD, and Outpatient Healthcare Utilization Among Veterans - Banducci, Anne N. (Psychol Serv, 2017)
Premature discontinuation of PTSD treatment is generally associated with poorer outcomes for veterans with PTSD. What is less clear is whether treatment benefits, as a function of treatment length, persist, as well as predict less future mental healthcare utilization. We sought to determine whether length of stay (LOS) in residential PTSD treatment predicted discharge PTSD symptom severity and outpatient mental healthcare utilization. We hypothesized discharge PCL scores would mediate the relations between LOS in residential treatment and outpatient mental healthcare utilization. The current study included 740 veterans who received residential PTSD treatment within five VA hospitals and completed intake and discharge assessments, including the PTSD Checklist (PCL). Information about LOS in residential treatment and outpatient mental healthcare utilization was obtained from the National Patient Care Database. We examined the relations between residential LOS, discharge PCL, and outpatient mental healthcare utilization. Non-parametric bootstrapping was utilized to test for the significance of the indirect effect. Veterans who stayed in residential treatment longer had lower PCL scores at discharge (Est.=−2.50, SE=.51, p<.001) and veterans with lower PCL scores at discharge sought fewer outpatient mental health visits (Est.=.31, SE=.14, p=.03). A bias-corrected bootstrap confidence interval for the indirect effect (ab=−.77) based on 10,000 bootstrap samples was entirely below zero (−1.72 to −.05). This indicates discharge PCL mediated the relations between LOS and outpatient mental healthcare utilization, such that individuals with a longer LOS in residential PTSD treatment had lower PCL scores at discharge and thus utilized less outpatient mental healthcare.